Ovarian Cancer Incidence in Iran and the World - Arab, Malihe; Noghabaei, Giti (Reports of Radiotherapy and Oncology, 2024)
Introduction: Ovarian cancer ranks the 8th cancer causing death in the world. This study aims to compare incidence rate of ovarian cancer in Iran with other countries. Materials and methods: Data from International Agency for Research on Cancer’s GLOBOCAN 2008 database is used to compare ovarian cancer age standard incidence rate from different parts of the globe considering the developing and developed regions. Results: Iran is among countries with low incidence of ovarian cancer and an age standard incidence rate of 3.07 in 2005 and 3.1 in 2008. Conclusions: Ovarian cancer is the most common gynecologic cancer in Iran. Various risk and protective factors of ovarian cancer might be clarified in Iran in order to prevent increasing incidence of this cancer in the future. At the present this disease is significant considering its disease burden